Differences in molecular characteristics and expression of virulence genes in carbapenem-resistant and sensitive Klebsiella pneumoniae isolates in Ningbo, China - Jiang, Min; Qiu, Xuedan; Shui, Siyi; Zhao, Rongqing; Lu, Wenjun; Lin, Chenyao; Tu, Yanye; Wu, Yifeng; Li, Qingcao; Wu, Qiaoping (Frontiers in Microbiology, 2024)
Background: In recent years, Klebsiella pneumoniae has attracted attention because of its increasing drug resistance. At the same time, the migration and pathogenicity caused by its virulence genes also bring many difficulties to the diagnosis and treatment of clinical infections. However, it is currently unclear whether there are differences in virulence and pathogenicity with changes in drug resistance. Objective: To understand the differences in molecular characteristics and expression of virulence genes in carbapenem-resistant Klebsiella pneumoniae (CRKP) and carbapenem-sensitive Klebsiella pneumoniae (CSKP). Methods: Using polymerase chain reaction (PCR), we examined capsule polysaccharide-related genes and virulence genes in 150 clinical isolates of CRKP and 213 isolates of CSKP from the local area in Ningbo, China. Multilocus sequence typing (MLST) was used to analyze the phylogenetic relationships of clinical Klebsiella pneumoniae isolates. Furthermore, real-time quantitative PCR (RT-qPCR) was used to analyze the expression differences of common virulence genes in CSKP and CRKP, and the virulence was further verified by the larval model of Galleria mellonella. Results: The study found that the detection rates of genes rmpA, iroB, peg-344, magA, aerobactin, allS, kfu, and entB were significantly higher in CSKP compared to CRKP. The capsule gene types K1 and K2 were more common in CSKP, while K5 was more common in CRKP. High-virulence Klebsiella pneumoniae (hvKP) was predominantly from CSKP. CRKP strains exhibited noticeable homogeneity, with ST11 being the predominant sequence type among the strains. CSKP strains showed greater diversity in ST types, but ST23 was still the predominant sequence type. Carbapenem-sensitive high-virulence Klebsiella pneumoniae (CS-hvKP) had higher expression of rmpA and rmpA2 genes compared to carbapenem-resistant high-virulence Klebsiella pneumoniae (CR-hvKP). In the wax moth virulence model, the survival rate of CS-hvKP was significantly lower than that of CR-hvKP.There is a significant difference in the distribution of virulence genes between CSKP and CRKP, with CSKP carrying a significantly greater number of virulence genes. Furthermore, compared to CSKP, CRKP strains exhibit noticeable homogeneity, with ST11 being the predominant sequence type among the strains. Additionally, in terms of virulence gene expression efficiency and virulence, CSKP is significantly higher than CRKP.